2005
DOI: 10.1002/jso.20277
|View full text |Cite
|
Sign up to set email alerts
|

The role of glial cell line‐derived neurotrophic factor (GDNF) and integrins for invasion and metastasis in human pancreatic cancer cells

Abstract: The enhancement of integrin expression by GDNF signaling through the GDNF receptor strongly influences invasion and adhesion to ECM proteins by pancreatic cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Moreover, GFRA1 (GDNF family receptor alpha-1) is a potent neurotrophic factor that plays a key role in the control of neuron survival and differentiation. Somewhere, this gene is introduced as a function of age [36]. Also, MTHFR (methylenetetrahydrofolate reductase) was proposed to participate in metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GFRA1 (GDNF family receptor alpha-1) is a potent neurotrophic factor that plays a key role in the control of neuron survival and differentiation. Somewhere, this gene is introduced as a function of age [36]. Also, MTHFR (methylenetetrahydrofolate reductase) was proposed to participate in metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A common finding in pancreatic adenocarcinoma is invasion of the intrapancreatic perineural space and the extrapancreatic retroperitoneal nerve plexus, and perineural invasion is an important prognosis factor in pancreatic cancer (8,62). Several lines of evidence have recently suggested that GDNF signaling may be associated with regulation of the invasive potential in human pancreatic cancer cells (27,28,64,82). The expression of MMP-2 and MMP-9 correlates with the degree of pancreatic cancer cell and lymphoid invasion (61,101), and GDNF stimulates both the expression and the enzymatic activity of MMP-9 in pancreatic cancer cells (64).…”
Section: Discussionmentioning
confidence: 99%
“…7 Cell migration has also shown to be increased by conditioned medium from GDNF-treated cells that expressed RET and GFRα1, and the increase in integrin expression induced by GDNF signalling through the GDNF receptor strongly influenced invasion and adhesion to the extracellular membrane by pancreatic cancer cells. 23 We conclude that GDNF may play an important role in the proliferation and metastasis of pancreatic cancer, especially in patients with perineural invasion. Furthermore, strongly positive expression of GDNF may be an indication for early intensified radiotherapy.…”
Section: Over-expression Of Gdnf and Ret In Pancreatic Cancermentioning
confidence: 69%